Assessing the indoor temperature and relative humidity through a passive cooling system adaptive from the Dromedary Camel's Nasal Mechanism (DCNM) - Gojar, Katya Claude E.; Puso, Mark Ndsy L. (2020)
With the increase of energy demands in using active cooling devices, the heat index of the country continues to increase. The cycle repeats and aggravates the drastic change in the country?s climate. Through understanding the biomimetic potential of the Dromedary Camel?s Nasal Mechanism, its processes can be adapted to a passive cooling system that addresses the heat index issue. The study aims to analyze the adaptation of the Dromedary Camel?s Nasal Mechanism to a passive cooling system and its comparison with a non passive cooling system through experimental research for both qualitative and quantitative approach. The analogies formulated from extensive research is then translated to architectural measures, particularly the utilization of the bamboo material in the passive cooling system. The data collected from the experiment The systems design guideline was derived from the results given the controlled circumstances and real time conditions. The outputs shows that the adapted passive cooling system improves the indoor room temperature to 2.19°C and 3.86% for relative humidity resulting to a decrease in heat index to 5.38°C.
Thesis (BS Architecture)--University of the Philippines Mindanao, 2020